Formulasi Kebijakan K2I di Bidang Perkebunan Kelapa Sawit - Khairul Anwar (Universitas Riau, 2011)
This study aims to find synergies decentralization policy formulation by taking the caseof policy conflicts management K2I oil palm plantations in Riau years 2005-2010. The method usedqualitative methods. Interactive method that covers data collection, data display, data verification,and withdrawal kesimpulan.This study found that first, the formulation of policy synergy acrossthe ministry after the regional autonomy is characterized by changing patterns of interaction ofbureaucrats, businessmen, politicians and local elites to the increasingly dynamic; Second, the actorsattempt to mobilize resources and conflicting preferences; Third, arenas and networks used by localelites increasingly overlap. The results of this study is expected to contribute to science and technologypolicy formulation in the form of synergy model, conflict mapping and plantation-based policyrecommendations for national and local governments in improving development policies in the future.